Penguatan Peran Perempuan dalam KUBE melalui Pendekatan Sociopreneurship: Studi Kasus pada KUBE Kerupuk Lomang Ubi Bersinar Kuok, Kabupaten Kampar - Frini Karina Andini; Bunga Chintia Utami; Yunandra Yunandra; Encik Rania Olivia; Riska Febrianda; Egi Chandra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Women has a strategic role in rural economic development, including in micro-business groups such as the Joint Business Group (KUBE). However, limited production skills, weak business management, inadequate financial recording, and traditional marketing strategies remain significant obstacles to improving competitiveness. This community service program was carried out at KUBE Kerupuk Lomang Ubi Bersinar Kuok, Kampar Regency, with a focus on strengthening women’s roles through a sociopreneurship approach. The implementation methods included training on production skills (quality control, SOP preparation, and product certification), facilitation of modern production equipment, training on business management and simple financial recording, as well as training on digital marketing strategies and product branding. The program was implemented in a participatory manner by involving female KUBE members, the village government, and Universitas Riau students through the MBKM program. The results showed an increase in production capacity of approximately 30%, the establishment of more organized financial records, and the adoption of digital marketing strategies that expanded market reach. Socially, women’s roles in KUBE were strengthened through the involvement of the Women Farmers’ Group as suppliers of raw materials, which contributed to greater independence and family economic contribution. Economically, KUBE members gained higher income and improved competitiveness of cassava-based products, a local specialty of Kuok.